PSYCHOLOGICAL CHARACTERISTICS OF ADOLESCENCE, PROBLEMS AND SOLUTIONS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
In this article, it is explained in detail that adolescence is a special period, that is, a period of transition, a complex period, a crisis period. In addition, the problems that arise in adolescents and their solutions are covered in detail.